Irrigated safflower at different phenological stages of Brazilian southeast dry season - Santos, Reginaldo Ferreira; Bassegio, Doglas; Silva, Marcelo de Almeida [UNESP]; Klar, Antonio Evaldo [UNESP]; Da Silva, Andreia Aparecida Ferreira [UNESP]; Da Silva, Tiago Roque Benetoli (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2019)
This study was conducted in order to determine the effect of irrigation regime imposed on development stages over safflower growth components (Carthamus tinctorius L.) in Engenheiro Coelho, SP, Brazil. The work was conducted in Arenic Hapludult soil. The experimental design was a completely randomized block with eight irrigation regimes and three replications. The irrigation regimes consisted of: water deficit (WD), irrigation at vegetative stage (V), irrigation at flowering stage (F), irrigation at grain formation stage (G), irrigation at vegetative and flowering phases (VF), irrigation in vegetative and grain formation stages (VG), irrigation at flowering and grain formation (FG) and irrigation in vegetative, flowering and grain formation stages (VFG) (control). The results of this study show that safflower is benefited by irrigation in vegetative period; however, irrigation is also effective when applied during flowering period in treatment under water deficit. Water shortage due to irrigation restriction during the vegetative stage reduces morphological components of safflower growth. The grain and oil yield is affected by water restriction in all safflower cultivation stages. Treatment with water availability throughout vegetative and flowering periods produced 895 kg ha –1 of grain yield.
Cártamo irrigado em diferentes estágios fenológicos na estação seca do sudeste brasileiro
Keywords: Carthamus tinctorius L; Oilseed; Plant growth; Water deficit